Primary Neuroendocrine Carcinoma of the Breast: Histopathological Criteria, Prognostic Factors, and Review of the Literature - Lena Marinova; Doroteya Malinova; Snezhinka Vicheva (Case Reports in Pathology)
We present here a case of a 42-year-old woman diagnosed with primary neuroendocrine carcinoma of the breast (NECB). We discuss the importance of histological criteria for primary neuroendocrine mammary carcinoma, established by WHO in 2003 and 2012. After an overview of different cases of primary neuroendocrine carcinoma of the breast published in the literature, we present information about differential diagnosis, prognostic factors, and surgical and adjuvant treatment. Prognosis of NECB is not different from that of other invasive breast carcinomas and the most important prognostic factor is tumor grade (G). There is no standard treatment and patients should be treated similarly to patients with invasive ductal carcinoma, NOS (not otherwise specified), whose choice of therapy depends on tumor’s size, degree of differentiation, clinical stage, and hormonal status.